2006
DOI: 10.1063/1.2214157
|View full text |Cite
|
Sign up to set email alerts
|

Detection of 0.5THz radiation from intrinsic Bi2Sr2CaCu2O8 Josephson junctions

Abstract: We report the detection of electromagnetic radiation at about 500GHz from current-biased intrinsic Bi2Sr2CaCu2O8 single crystal Josephson junctions. We used two silicon lenses to quasioptically couple radiation from our samples to an integrated superconducting heterodyne receiver. The estimated maximum Josephson radiation power which reached the receiver antenna was about 1pW. We attribute the observed radiation to individual Josephson junctions of the stack and discuss a possibility of the phase locking of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 23 publications
2
62
0
Order By: Relevance
“…7 We succeeded in observation of the intense power of EM emission of $5 lW, which have never been achieved before. It is indeed 5-6 orders of magnitude stronger than that from single Josephson junction, and even a couple of orders of magnitude stronger than the previous reports [3][4][5]. For the emission it is required to fulfill two conditions: Eqs.…”
Section: Discussionmentioning
confidence: 95%
“…7 We succeeded in observation of the intense power of EM emission of $5 lW, which have never been achieved before. It is indeed 5-6 orders of magnitude stronger than that from single Josephson junction, and even a couple of orders of magnitude stronger than the previous reports [3][4][5]. For the emission it is required to fulfill two conditions: Eqs.…”
Section: Discussionmentioning
confidence: 95%
“…Experimentally, radiation from the high-temperature layered superconductor BSCCO at relatively low frequencies, 7-16 GHz, was detected by Hechtfischer et al [29]. Some indirect evidence of radiation at higher frequencies has been recently reported by Kadowaki et al [30] and Batov et al [31] reported radiation at the frequency 0.5 THz with power 1 pW from BSCCO mesa consisting 100 junctions in zero dc magnetic field.…”
Section: Introductionmentioning
confidence: 95%
“…Radiation from BSCCO with injection of quasiparticles has been reported [20,21,22,23,24]. Alternatively, the terahertz radiation without a magnetic field has also been attempted [25,26,27,28,29]. Recently, a strong coherent radiation from BSCCO in the absence of a magnetic field was observed [27,29], where the mesa of the single crystal of BSCCO forms a cavity.…”
Section: Introductionmentioning
confidence: 99%